Dibasic Magnesium Hypochlorite as an Oxidant to Tune Pasting Properties of Potato Starch in One Step - Broekman, J. O. P.; Dijkhuis, Brian W.; Thomann, Johanna A.; Heeres, André; Heeres, Hero J.; Deuss, Peter J. (ChemEngineering, 2023)
Modified starches are used widely in the food industry but often have a low nutritional value, lacking minerals vital for the human body, such as magnesium. Magnesium addition to native starches has been shown to result in changes in pasting properties. However, little work has been done on the addition of magnesium and other divalent cations to highly oxidised starches. In this work, we used dibasic magnesium hypochlorite (DMH) to oxidise potato starch to an industrially relevant degree of oxidation while at the same time introducing magnesium into the starch structure. We found that magnesium incorporation changes the pasting properties of starch and increases the gelatinisation temperature significantly, possibly due to an ionic cross-linking effect. These properties resemble the properties found for heat-moisture-treated potato starches. This change in properties was found to be reversible by performing a straightforward exchange of metal cations, either from sodium to magnesium or from magnesium to sodium. We show in this work the potential of the addition of divalent cations to highly oxidised starches in modifying the rheological and pasting properties of these starches and at the same time adding possible health benefits to modified starches by introducing magnesium.